PLAN DE PRODUCCIÓN PARA LA COMUNIDAD DE JARATENTA PERTENECIENTE A LA PARROQUIA TENTA CANTÓN SARAGURO - Contento Japón, Jorge Pachacutic (2016)
Agricultural activities in the parish San Pablo de Tenta climate floors, are developed with certain crops depending on the site and the areas. The Jaratenta community is a sector that is closely related to the ecological conditions of the various zones with the characteristics of the soils, the relief, the altitude, the availability of irrigation, cultural factors, requirements for obtaining products for consumption and production for market purposes, which constitute the economic base of the agricultural producers of the community needs. The present study aims to develop a production Plan for the community of belonging to the parish Tenta Jaratenta canton Saraguro. In order to make a socio-productive diagnosis of the community and develop a plan of production with the best agricultural alternatives existing in the community of Jaratenta. The research was carried out in the community of Jaratenta, according to data from the Census of population and housing in the year 2010, granted by the INEC, households that have housing are 42 families; which has been taken as a basis of information for this study. This was believed convenient to use the method of data collection, through the application of a census to all families in the community, for which a questionnaire was designed to gather information pertaining to production, a procedure where it is given to know the different steps of the development of the research was also used. The development of this research surveys were applied to families in the community of Jaratenta where the sectors of production, both the upper and the lower part is witnessed, could also be seen that products that are cultivated more in the lower part are the avocado, corn, and potatoes; and at the top the potato, maize, and tree tomato. Most of this production is intended for sale and consumption. Most of the families in the community have spaces without and with irrigation system and are. Willing to work on a plan of production improvement with the aim of improving the production and therefore the economy of the family. Conducting this investigation is concluded, a time carried out a diagnostic socio-productive, where took into consideration three major products such as tree tomato, passion fruit and the babaco, where determined product of higher performance, as it is the cultivation of the organic rack.